Treating children and adolescents with multiple traumas: a randomized clinical trial of narrative exposure therapy. Issue 1 (31st December 2019) - Peltonen, Kirsi; Kangaslampi, Samuli
ABSTRACT: Background and Objective : Millions of children and adolescents worldwide suffer from post-traumatic stress disorder (PTSD) and other problems due to prolonged exposure to traumatizing events. Forms of cognitive-behavioural therapy are the most commonly used treatment for PTSD, but evidence from sophisticated studies in clinical settings among children is limited. Method : This multicentre, parallel, non-blinded, pragmatic randomized controlled trial assessed the effectiveness of narrative exposure therapy (NET) in traumatized children and adolescents. Fifty 9–17-year-old participants, who had experienced prolonged traumatic conditions in the form of refugeedom or family violence and suffered from PTSD symptoms, were randomized into NET ( n = 29) and treatment as usual (TAU; n = 21) active control groups. The objective was to determine whether NET can be feasibly implemented within the existing healthcare system of a high-income country and whether it would reduce mental health problems, especially PTSD, and increase resilience, in children and adolescents with multiple traumas more effectively than TAU. We hypothesized that NET would be more effective than TAU in reducing symptoms and increasing resilience. Results : Analysis of variance revealed that PTSD and psychological distress, but not depression symptoms, decreased regardless of treatment group. Resilience increased in both groups. Within-group analyses showed that the decrease in PTSD symptoms was significant in the NET group only. The effect sizes were large in NET but small in TAU. Concerning PTSD symptom cut-off scores, the reduction in the share of participants with clinical-level PTSD was significant in the NET group only. Intention-to-treat analyses using linear mixed models confirmed these results. Conclusions : Despite its shortcomings, this study gives preliminary support for the safety, effectiveness, and usefulness of NET among multiply traumatized children and adolescents in clinical settings. Close attention must be paid to the implementation of the new intervention as an everyday tool in healthcare. HIGHLIGHTS: Narrative exposure therapy (NET) is a safe and useful method for treating children with multiple violence-related traumas. Intrusive symptoms may be more effectively treated with NET than with non-exposure-based methods. Close attention must be paid to the implementation of new interventions for trauma-related symptoms as everyday tools in typical healthcare settings.